A Congenital Case of Ependymoblastoma: A Rare and Aggressive Brain Tumor. Issue 1 (January 2019) - Grassham, Courtney D.; Rady, Sara; Foster, Kimberly; SantaCruz, Karen S.; Kuttesch, John F.; Maxwell, Jessie R.
Abstract : Congenital brain tumors are rare, representing <2% of all childhood brain tumors. Of these, ependymoblastoma is a profoundly aggressive embryonal brain tumor that is included in the diagnostic entity known as an embryonal tumor with multilayered rosettes. This report of a congenital ependymoblastoma diagnosed at birth aims to highlight how much remains unknown about embryonal tumor with multilayered rosettes and the devastating prognosis of this condition. Despite recent advancements made in identifying molecular targets for therapy, this tumor continues to have a high rate of recurrence with few successful treatment options, especially when diagnosed in the newborn period.